1963
DOI: 10.1002/art.1780060111
|View full text |Cite
|
Sign up to set email alerts
|

Management of the rheumatoid patient

Abstract: N WORDING this topic, the Editor has invited a nice distinction. There I is no definitive therapy for rheumatoid arthritis, if indeed this polymorph disease proved to be a single entity. But we are usually agreed on what constitutes a rheumatoid patient, and we firmly think that we can help most of them though we cannot promise or prove it. Within these limits, what are the goals we may reasonably pursue in their management? AIMSOne predictable result over the long stretch is a fair capacity for useful work an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1966
1966
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Clinical trials involving estrogen suppletion in RA have led to conflicting reports. Early studies, without placebo-controlled treatment groups, demonstrated efficacy of estrogen treatment in RA [50,51]. In placebo-controlled trials, however, different outcomes were documented.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials involving estrogen suppletion in RA have led to conflicting reports. Early studies, without placebo-controlled treatment groups, demonstrated efficacy of estrogen treatment in RA [50,51]. In placebo-controlled trials, however, different outcomes were documented.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment program for rheumatoid patients was reviewed (283,345,864,1101,1303) arid past therapeutic trials, con-[rolled or otherwise, were discussed in critical detail (1370). New studies of two classic remedies, rest and salicylates, were especially welcome.…”
Section: Generalmentioning
confidence: 99%
“…The value and even necessity of blood levels in controlling salicylate dosage was emphasized (30,1303). Tinnitus may be an unreliable guide to toxicity.…”
Section: Salicy Latesmentioning
confidence: 99%